Penerimaan Mahasiswa terhadap Aplikasi Accurate Berdasarkan Model Technology Readiness and Acceptance (TRAM) - Evieana R Saputri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze the factors influencing students’ acceptance of the Accurate accounting application using the Technology Readiness and Acceptance Model (TRAM) approach. The model integrates personality dimensions from the Technology Readiness Index (TRI)—optimism, innovativeness, discomfort, and insecurity—with the main constructs of the Technology Acceptance Model (TAM), namely perceived ease of use and perceived usefulness. Data were collected through questionnaires distributed to 92 students of Politeknik YKPN Yogyakarta who had participated in the Certified Accurate Professional (CAP) certification exam and analyzed using the SEM-PLS method. The results show that optimism and innovativeness have a positive and significant effect on perceived ease of use, while optimism also has a significant effect on perceived usefulness. In contrast, discomfort and insecurity were found to have no significant effect on either perception. These findings highlight that positive personality traits such as optimism and innovativeness play a dominant role in shaping users’ perceptions of technology acceptance, whereas psychological barriers tend to be insignificant. This research provides empirical contributions for higher education institutions in developing strategies to enhance students’ technological readiness, particularly through training and learning activities based on accounting applications, to support success in certification examinations.